Factors influencing the use of Buy Now Pay Later (BNPL) payments - Krzysztof Waliszewski; Małgorzata Solarz; Jakub Kubiczek (Contemporary Economics, 2024)
This article focuses on the fastest-growing consumer credit segment usually associated with e-commerce, but increasingly offered for brick-and-mortar shopping too. The purpose of the study was to identify how, and the extent to which, specific aspects of consumer behaviour - particularly in terms of attitudes towards money management, and socio-demographics - influence the use of BNPL. The reasons are socio-demographic, economic, psychological and technological. The article incorporates a broad literature review of the motives behind consumers' use of BNPL as well as an original empirical survey among a representative sample of Poles, conducted using the CAWI technique. The impact and strength of individual factors for choosing BNPL were identified via a logistic regression model. The statistical significance of the selected variables was then evaluated, followed by the elimination of non-significant variables from the model. It helped select statistically significant factors for using BNPL. Among 7 statistically significant variables, 3 relate to socio-demographic features of the respondents - level of education, income and gender. Personal innovativeness, inclination towards going into debt, as well as a family history of taking various loans slightly increase the probability of opting for BNPL. It had been presumed that propensity to save would have a negative effect, and that optimism would have a positive influence, on choosing BNPL; however, this presumption was not demonstrated. Nor do consumerism and impulsiveness in making purchases affect the likelihood of using BNPL. Of all the statistically significant factors underlying decisions to choose BNPL, the consumer's use of LendTech has the greatest impact, increasing the chance of using BNPL. This suggests that similar consumers constitute these two segments. LendTech (lending technology) is defined as part of the FinTech (financial technology) sector, which concerns the granting of digital loans by non-bank lending institutions in remote channels (Waliszewski et al, 2024).
Keywords: D1; D15; O33; 330; buy-now-pay-later (BNPL); FinTech; LendTech; consumer finance; retail payments